NK cells expansion in vitro is followed by loss of inhibitory KIR expression - N. A. Alekseeva; M. O. Ustyuzhanina; M. A. Streltsova; M. V. Grechikhina; G. V. Lutsenko; E. I. Kovalenko (Медицинская иммунология, 2023)
NK cells are innate lymphocytes that are able to eliminate altered cells, which makes them promising for the immunotherapy of viral diseases and tumors. The NK cell population is characterized by high phenotypic and functional diversity. In particular, in the pool of highly differentiated NK cells in the presence of cytomegalovirus (HCMV), a population of adaptive cells can be formed, characterized by a high lifespan and high cytotoxicity. However, in order to carry out a cytotoxic reaction, a NK cell must undergo a licensing process, during which it acquires the expression of NKG2A and KIRs. Currently, there are many effective methods of NK cell accumulation for subsequent use in therapy, one of them is the stimulation with IL-2 and K562-mbIL21 feeder cells. Highly differentiated adaptive-like NK cells are able to expand in respond to such stimulation. However, the phenotype of actively expanding NK cells dynamically changes. Loss of inhibitory KIR expression during intense proliferation of NK cells may adversely affect their cytotoxic potential. This work shows that highly differentiated CD56dimNKG2C+ NK cells from HCMV-seropositive individuals have a high proportion of KIR2DL2/3+ cells. This may indicate a high stability of KIR receptor expression in this population. We have shown that CD56dimNKG2C+ clonal cultures obtained by stimulation with IL-2 and K562- mbIL21 are characterized by high stability of KIR2DL2/3 expression compared to NKG2C-negative and less differentiated CD56brightNKG2C+. Also, in heterogeneous cultures of adaptive NK cells precursors CD57- CD56dimNKG2C+, a higher expression level of KIR2DL2/3 was observed in comparison with NKG2C-negative cultures of CD57-CD56dimNKG2C-. Thus, the accumulation of NK cells upon stimulation with IL-2 and K562- mbIL2 feeder cells can lead to loss of expression of KIR receptors and a decrease in their functional activity. However, cultures of highly differentiated NK cells of HCMV-seropositive individuals CD56dimNKG2C+, as well as cultures of precursors of adaptive NK cells CD57-CD56dimNKG2C+, are characterized by a greater stability of KIR2DL2/3 expression. As a result, stimulation with IL-2 and K562-mbIL21 feeder cells can be used to accumulate adaptive-like cells and their progenitors with stable inhibitory KIR expression and high cytotoxic potential.